2021
DOI: 10.3390/met11040550
|View full text |Cite
|
Sign up to set email alerts
|

Application of Low Melting Metals for Separation of Uranium and Zirconium in a “Fused Chloride—Liquid Alloy” System

Abstract: Closeness of electrochemical properties of uranium and zirconium makes separation of these metals in pyroelectrochemical reprocessing of spent nuclear fuels a challenging task. Varying electrode material can change metals’ deposition potentials. The study was aimed at assessing the effect of the cathode material on deposition potentials of zirconium and uranium from 3LiCl–2KCl based melts. Solid (tungsten) and liquid (gallium, zinc, Ga–Zn, Ga–Sn and Ga–In alloy) working electrodes were tested at 532–637 °C. Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Currently much attention is paid to the analysis of the zirconium electrochemistry in molten LiCl-KCl, which is suggested as a possible electrolyte for the large scale pyrochemical processing of spent nuclear fuel (SNF) [12][13][14][15][16][17][18][19]. A new chlorination method of rare earth oxides (La 2 O 3 , CeO 2 , Nd 2 O 3 , Y 2 O 3 ) and actinide oxides (UO 2 and PuO 2 ), which implies gaseous ZrCl 4 in molten LiCl-KCl, is being developed and tested for the pyrometallurgical processing of SNF [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Currently much attention is paid to the analysis of the zirconium electrochemistry in molten LiCl-KCl, which is suggested as a possible electrolyte for the large scale pyrochemical processing of spent nuclear fuel (SNF) [12][13][14][15][16][17][18][19]. A new chlorination method of rare earth oxides (La 2 O 3 , CeO 2 , Nd 2 O 3 , Y 2 O 3 ) and actinide oxides (UO 2 and PuO 2 ), which implies gaseous ZrCl 4 in molten LiCl-KCl, is being developed and tested for the pyrometallurgical processing of SNF [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Currently used hydrometallurgical methods of reprocessing SNF involve the formation of concomitant liquid waste, the amount of which is difficult to reduce. In view of this problem, the “dry” methods of SNF processing such as fluoride volatility [ 21 ], pyroelectrochemical [ 22 , 23 , 24 ], and plasma methods [ 25 , 26 , 27 ] have received active development. The latter are modern developments of the aforementioned electromagnetic methods of mass separation, the principles of which were developed in the middle of the 20th century [ 9 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the fission of U and Pu, several isotopes of zirconium are formed 8 . By its electrochemical properties, in particular, by the value of the standard apparent electrode potential, zirconium is the closest to uranium among all elements of FPs 9 . It was shown that a Ga‐Zn cathode gives a high efficiency of separation of uranium from zirconium at using chloride melts 9 .…”
Section: Introductionmentioning
confidence: 99%
“…By its electrochemical properties, in particular, by the value of the standard apparent electrode potential, zirconium is the closest to uranium among all elements of FPs 9 . It was shown that a Ga‐Zn cathode gives a high efficiency of separation of uranium from zirconium at using chloride melts 9 . Attempts are currently being made to separate alkali metals (AMs) and alkaline earth (AE) metals by the electrolytic reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation